ChemInform Abstract: RbjMk[Fe(CN)6]l (M: Co, Ni) Prussian Blue Analogue Hollow Nanocubes: A New Example of a Multilevel Pore System. Issue 13 (18th March 2013) - Risset, Olivia N.; Knowles, Elisabeth S.; Ma, Shengqian; Meisel, Mark W.; Talham, Daniel R.
Abstract Uniform Rb0.4M4 [Fe(CN)6]2.8·7.2H2O (M: Co, Ni) hollow nanoparticles are prepared by dissolving Rb1.6Mn4[Fe(CN)6]3.2 ·4.8H2O@Rb0.4M4 [Fe(CN)6]2.8·7.2H2 O core@shell heterostructures in water (45 °C, 45 min, 80 and 78% yield for the Co and Ni compounds, respectively).